Downregulation of nuclear STAT2 protein in the spinal dorsal horn is involved in neuropathic pain following chronic constriction injury of the rat sciatic nerve - Huang, Zhifeng; Ding, Zijing; Xu, Yangting; Xi, Caiyun; He, Liqiong; Luo, Hui; Guo, Qulian; Huang, Changsheng (Frontiers in Pharmacology, 2023)
Regulation of gene transcription in the spinal dorsal horn (SDH) plays a critical role in the pathophysiology of neuropathic pain. In this study, we investigated whether the transcription factor signal transducer and activator of transcription 2 (STAT2) affects neuropathic pain and evaluated its possible mechanisms. A proteomic analysis showed that the nuclear fraction of STAT2 protein in the SDH was downregulated after chronic constriction injury of the rat sciatic nerve, which was associated with the development of neuropathic pain. Similarly, siRNA-induced downregulation of STAT2 in the SDH of naïve rats also resulted in pain hypersensitivity. Using RNA-sequencing analysis, we showed that reduction of nuclear STAT2 after chronic constriction injury was associated with increased expression of microglial activation markers, including the class II transactivator and major histocompatibility complex class II proteins. In addition, siRNA-induced downregulation of STAT2 promoted microglial activation and pro-inflammatory cytokine expression in the SDH. Taken together, these results showed that chronic constriction injury caused downregulation of nuclear STAT2 in the SDH, which may result in microglial activation and development of neuropathic pain. Our findings indicate that restoration of nuclear expression of STAT2 could be a potential pathway for the treatment of neuropathic pain.